If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(2x-2)=8x+40
We move all terms to the left:
-6(2x-2)-(8x+40)=0
We multiply parentheses
-12x-(8x+40)+12=0
We get rid of parentheses
-12x-8x-40+12=0
We add all the numbers together, and all the variables
-20x-28=0
We move all terms containing x to the left, all other terms to the right
-20x=28
x=28/-20
x=-1+2/5
| 4{z-74}=44 | | 5{b+3}=55 | | 2=w/7-1 | | 2=g-83/5 | | 2x÷3+3x÷3=x÷3+8÷3 | | 13x7=5x+1 | | q/2+9=13 | | -12=(-2x+8) | | 2y+5=-7-2y | | a/2=3+2/7 | | a/3=1/10 | | d/3+1=2 | | 3(2e+4)=6e+12 | | 24=k273/2 | | x/100=15/40 | | 6(y+2)-4(y-1)=26 | | 210x=-675 | | 2x+(3x-1)=(137-x) | | 4=2-5b/7 | | 3.1=-4.7v-1.5v | | 2b/7-2=4 | | b/7+2=4 | | 3(t+1)=2t-6 | | -3t+5=0 | | 63=9b+54 | | 320r=2104 | | -1/6n=-1/15 | | 6x3=(9x5)-(9x2) | | (2-2x)/11=-12 | | 2(x-x)=36 | | 4t=-7+2t | | -29/12=-3/2n+3/2=7/6 |